Assessing the Microcirculation With Handheld Vital Microscopy in Critically Ill Neonates and Children: Evolution of the Technique and Its Potential for Critical Care - Erdem, Özge; Ince, Can; Tibboel, Dick; Kuiper, Jan Willem (Frontiers in Pediatrics, 2019)
Assuring adequate tissue oxygenation in the critically ill, but still developing child is challenging. Conventional hemodynamic monitoring techniques fall short in assessing tissue oxygenation as these are directed at the macrocirculation and indirect surrogates of tissue oxygenation. The introduction of handheld vital microscopy (HVM) has allowed for the direct visualization of the microcirculation and with this has offered insight into tissue oxygenation on a microcirculatory level. Since its introduction, technical improvements have been made to HVM, to both hardware and software, and guidelines have been developed through expert consensus on image assessment and analysis. Using HVM, the microcirculation of the skin, the buccal mucosa, and the sublingual mucosa of healthy and (critically) ill neonates and children have been visualized and investigated. Yet, integration of HVM in hemodynamic monitoring has been limited due to technical shortcomings. Only superficial microcirculatory beds can be visualized, inter-observer and intra-observer variabilities are not accounted for and image analysis happens offline and is only semi-automated and time-consuming. More importantly, patients need to be cooperative or fully sedated to prevent pressure and movement artifacts, which is often not the case in children. Despite these shortcomings, observational research with HVM in neonates and children has revealed the following: (1) age-related developmental changes in the microcirculation, (2) loss of hemodynamic coherence, i.e. microcirculatory disturbances in the presence of a normal macrocirculation and, (3) microcirculatory disturbances which were independently associated with increased mortality risk. Although these observations underline the importance of microcirculatory monitoring, several steps have to be taken before integration in the decision process during critical care can happen. These steps include technological innovations to ease the use of HVM in the pediatric age group, measuring additional functional parameters of microvascular blood flow and integrated automated analysis software. As a next step, reference values for microcirculatory parameters need to be established, while also accounting for developmental changes. Finally, studies on microcirculatory guided therapies are necessary to assess whether the integration of microcirculatory monitoring will actually improve patient outcome. Nevertheless, HVM remains a promising, non-invasive tool to help physicians assure tissue oxygenation in the critically ill child.